Gammarus-Microbial Interactions: A Review. (20th July 2011) - Nelson, Daniel
Abstract : Gammarus spp. are typically classified as shredders under the functional feeding group classification. In the wild and in the laboratory, Gammarus spp. will often shred leaves, breaking them down into finer organic matter fractions. However, leaf litter is a poor quality food source (i.e., high C : N and C : P ratios) and very little leaf material is assimilated by shredders. In freshwater habitats leaf litter is colonized rapidly (within ~ 1-2 weeks) by aquatic fungi and bacteria, making the leaves more palatable and nutritious to consumers. Several studies have shown that Gammarus spp. show preference for conditioned leaves over nonconditioned leaves and certain fungal species to others. Furthermore, Gammarus spp. show increased survival and growth rates when fed conditioned leaves compared to non-conditioned leaves. Thus, Gammarus spp. appear to rely on the microbial biofilm associated with leaf detritus as a source of carbon and/or essential nutrients. Also, Gammarus spp. can have both positive and negative effects on the microbial communities on which they fed, making them an important component of the microbial loop in aquatic ecosystems.